Scaffolding for Slow Learner Children on Integer Operations - Susilo, Christina Yulia; Prihatnani, Erlina (Kreano, Jurnal Matematika Kreatif-Inovatif, 2022)
Slow learners have lower grasping power, but that doesn't mean they don't have the same learning opportunities as children in their age group. This qualitative research aims to identify difficulties, design and apply scaffolding to slow learners in integers. The subject is slow learner student who is in class VIII Junior High School. Data collection techniques in this study are test, interview and documentation. The results showed that the subject inability to interpret the basic concepts of integers, jump count, compare integers, addition and subtraction on integers. Scaffolding that has been successfully used to help that difficulties is scaffolding for effective handling, goal-oriented and manipulative media. The assistance provided must be contextual, concrete, logical and not in the form of instructions with long sentences. Pictures, videos, representative activities and manipulative media that can be used repeatedly by the subject also succeeded in helping him understand the concept of integers.Anak slow learner memiliki daya tangkap lebih lambat, namun bukan berarti mereka tidak memiliki kesempatan belajar yang sama seperti anak-anak pada kelompok usianya. Penelitian kualitatif ini bertujuan untuk mengidentifikasi kesulitan, merancang dan menerapkan scaffolding terhadap slow learner pada bilangan bulat. Subjek adalah siswa ABK slow learner yang berada di kelas VIII SMP Negeri 1 Salatiga. Teknik pengumpulan data dalam penelitian ini adalah teknik tes, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa subjek mengalami  ketidakmampuan memaknai   konsep dasar bilangan bulat negatif, menentukan konsep hitung loncat, membandingkan bilangan bulat, melakukan operasi penjumlahan dan pengurangan bilangan bulat. Scaffolding yang berhasil membantu kesulitan ABK adalah scaffolding penanganan secara efektif, berorientasi pada tujuan serta media manipulatif. Bantuan yang diberikan harus bersifat kontekstual, konkret, logis dan tidak berupa instruksi dengan kalimat yang panjang. Gambar, video, aktivitas representatif serta media manipulative yang dapat digunakan berulang oleh subjek juga berhasil membantunya dalam memahami konsep bilangan bulat.